Chinese herbal medicine hot compress based on midnight-noon ebb-flow theory in relief of postoperative gastrointestinal dysfunction in a patient undergoing abdominal gynecological surgery and related nursing management (基于子午流注理论的中药热奄包改善妇科腹部手术后胃肠功能紊乱1例的护理) - SHEN Yueyue (申月月); ZHU Lei (朱磊); TANG Ling (唐玲); XU Jingjin (徐京巾); LU Ying (卢英) (中西医结合护理)
This paper summarized treatment and nursing experience of Chinese herbal medicine hot compress based on midnight-noon ebb-flow theory in relief of postoperative gastrointestinal dysfunction in a patient undergoing abdominal gynecological surgery and related nursing management. Nurses were educated about time selection of hot compress based on midnight-noon ebb-flow theory, operation procedure and precautions. Other targeted nursing interventions on diet and living habits were carried out to relieve the postoperative gastrointestinal dysfunction and improve the recovery. (本文总结了基于子午流注理论的中药热奄包热敷改善1例妇科开腹手术患者术后胃肠功能紊乱的护理经验, 包括确定中药热奄包热敷的时间点、热敷操作方法和注意事项, 以及饮食护理、生活护理等, 通过针对性干预, 进而有效改善患者的胃肠功能, 促进患者康复。)